Effect of High‐Caloric Nutrition on Survival in Amyotrophic Lateral Sclerosis. Issue 2 (6th January 2020) - Ludolph, Albert C.; Dorst, Johannes; Dreyhaupt, Jens; Weishaupt, Jochen H.; Kassubek, Jan; Weiland, Ulrike; Meyer, Thomas; Petri, Susanne; Hermann, Andreas; Emmer, Alexander; Grosskreutz, Julian; Grehl, Torsten; et al.
Abstract : Objective: Weight loss has been identified as a negative prognostic factor in amyotrophic lateral sclerosis, but there is no evidence regarding whether a high‐caloric diet increases survival. Therefore, we sought to evaluate the efficacy of a high‐caloric fatty diet (HCFD) for increasing survival. Methods: A 1:1 randomized, placebo‐controlled, parallel‐group, double‐blinded trial (LIPCAL‐ALS study) was conducted between February 2015 and September 2018. Patients were followed up at 3, 6, 9, 12, 15, and 18 months after randomization. The study was performed at 12 sites of the clinical and scientific network of German motor neuron disease centers (ALS/MND‐NET). Eligible patients were randomly assigned (1:1) to receive either HCFD (405kcal/day, 100% fat) or placebo in addition to riluzole (100mg/day). The primary endpoint was survival time, defined as time to death or time to study cutoff date. Results: Two hundred one patients (80 female, 121 male, age = 62.4 ± 10.8 years) were included. The confirmatory analysis of the primary outcome survival showed a survival probability of 0.39 (95% confidence interval [CI] = 0.27–0.51) in the placebo group and 0.37 (95% CI = 0.25–0.49) in the HCFD group, both after 28 months (point in time of the last event). The hazard ratio was 0.97, 1‐sided 97.5% CI = −∞ to 1.44, p = 0.44. Interpretation: The results provide no evidence for a life‐prolonging effect of HCFD for the whole amyotrophic lateral sclerosis population. However, post hoc analysis revealed a significant survival benefit for the subgroup of fast‐progressing patients. ANN NEUROL 2020;87:206–216